First Report of Campylobacter hepaticus Isolation in Laying Hens and Broiler Breeders with Spotty Liver Disease in Costa Rica - Quesada-Vásquez, Dioney (2023)
Poultry producers in Costa Rica have informally reported a spotty liver disease–like syndrome for more than 20 yr. However, despite many attempts, the infectious agent responsible for this syndrome had not been identified. Therefore, following current knowledge of spotty liver disease diagnosis, we invited veterinarians and poultry producers to submit samples to the diagnostic laboratories of the Veterinary Medicine School, Universidad Nacional, to identify the infectious agent of this syndrome. Veterinarians and poultry producers were instructed to collect gallbladders and livers aseptically and send them for pathology examinations and bacterial cultures in less than 24 hr after collection. Samples were processed for standard histopathologic studies and cultured under aerophilic, anaerobic, and microaerophilic conditions. Campylobacter-like colonies were isolated and identified by biochemical and PCR tests. Here we report for the first time the isolation, biochemical characterization, and molecular confirmation of Campylobacter hepaticus in laying hens and broiler breeders with spotty liver disease in Costa Rica.